RETRACTED: Curcumin Improves Palmitate-Induced Insulin Resistance in Human Umbilical Vein Endothelial Cells by Maintaining Proteostasis in Endoplasmic Reticulum - Mao Ye; Mao Ye; Hong Qiu; Yingkang Cao; Min Zhang; Yan Mi; Jing Yu; Changhua Wang (Frontiers Media S.A., 2017)
Dysfunction of proteasome and autophagy will result in disturbance of endoplasmic reticulum (ER) proteostasis, and thus lead to long-term and chronic ER stress and subsequent unfolded protein response (UPR), which is implicated in the occurrence and development of insulin resistance. Curcumin exerts beneficial metabolic effects in in vitro cells and in vivo animal models of diabetes and diabetic complications including cardiovascular diseases, due to its powerful anti-oxidative and anti-inflammatory properties. However, its impacts on insulin resistance of endothelial cells and its underlying mechanism(s) remain ill-defined. Herein, we tested the hypothesis that curcumin action in ER protein quality control was related to improvement of insulin resistance in human umbilical vein endothelial cells (HUVECs) cultured with saturated fatty acid palmitate. We found that palmitate treatment induced insulin resistance of HUVECs and activated both the ubiquitin-proteasome system (UPS) and autophagy. Palmitate-stimulated activation of the UPS and autophagy was attenuated by pharmacological inhibition of ER stress. In addition, curcumin supplementation mitigated palmitate-induced insulin resistance, inhibited the UPS, and activated autophagy. Furthermore, curcumin administration suppressed palmitate-induced protein aggregation and ER stress. Genetic inhibition of autophagy by silencing autophagy protein 5 (Atg5) completely restored total protein ubiquitination and protein aggregation in HUVECs treated with combined curcumin and palmitate. Atg5-knockdown also abolished the beneficial effects of curcumin on palmitate-induced ER stress, JNK/IRS-1 pathway as well as insulin signaling. Our results reveal that curcumin-activated autophagy could maintain proteostasis in ER leading to attenuation of ER stress and subsequent inhibition of JNK/IRS-1 pathway and improvement of insulin resistance.